POWER IN INDONESIAN PRESIDENTIAL SPEECHES: AN ANALYSIS OF LINGUISTIC MODALITY - Jannatussholihah, Siti; Triyono, Sulis (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
This paper discusses the relationship between the language and power in the presidential speech text, which is projected through linguistic features, especially modalities. The data was obtained from a speech delivered by President Joko Widodo during the plenary session of the Indonesian People's Consultative Assembly (MPR RI) for the inauguration of the elected president for the 2019-2024 period and the delivery of the president's vision for Indonesia better. Analysis of this paper from linguistic modalities uses a three-dimensional model of Fairclough's critical discourse (CDA) analysis to answer its research questions. The results show that Jokowi used several linguistic modal verbs in projecting his strength. Based on the modality's context, it can be understood that the president conveyed his strategic desire to be himself when he tried to connect with the audience and build his image, audience, and relationship. The President produces a discourse that embodies assumptions about his leadership and audience's social relationship and affirms his legal authority as president and his power. Through the language used, Jokowi creates, maintains, and explains power he holds in these forums.